Balancing Infrastructure for the Airport Metropolis - Keast, R.; Baker, D.; Brown, Kerry (Institute of Electrical and Electronics Engineers ( IEEE, 2008)
Ongoing financial, environmental and political adjustments, have shifted the role of large international airports. Many airports are expanding from a narrow concentration on operating as transportation centres to becoming economic hubs. By working together, airports and industry sectors can contribute to and facilitate not only economic prosperity, but create social advantage for local and regional areas in new ways. This transformation of the function and orientation of airports has been termed the aerotropolis or airport metropolis, where the airport is recognised as an economic centre with land uses that link local and global markets. This paper contends that the conversion of an airport into a sustainable airport metropolis requires more than just industry clustering and the existence of hard physical infrastructure. Attention must also be directed to the social infrastructure within proximate areas and the maximisation of connectivity flows within and between infrastructure elements. It concludes that the establishment of an interactive and interdependent infrastructure trilogy provides the necessary balance to the airport metropolis to ensure sustainable development. This paper provides the start of an operating framework to integrate and harness the infrastructure trilogy to enable the achievement of optimal and sustainable social and economic advantage from airport cities.